2013
DOI: 10.3390/ma6020551
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Research on Thermal Shock Resistance of Ultra-High Temperature Ceramics Focusing on the Adjustment of Stress Reduction Factor

Abstract: The thermal shock resistance of ceramics depends on not only the mechanical and thermal properties of materials, but also the external constraint and thermal condition. So, in order to study the actual situation in its service process, a temperature-dependent thermal shock resistance model for ultra-high temperature ceramics considering the effects of the thermal environment and external constraint was established based on the existing theory. The present work mainly focused on the adjustment of the stress red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…So R is the lower limit of the critical rupture temperature difference. In addition, although the second TSR parameter R' can reflect both mechanical properties and the thermal conductivity of materials, it still can't characterize the TSR correctly in many situations [18,28,29]. So the heat transfer condition and critical rupture temperature difference are used to characterize the TSR of ZnS plate in the calculation [24,25].…”
Section: Resultsmentioning
confidence: 98%
“…So R is the lower limit of the critical rupture temperature difference. In addition, although the second TSR parameter R' can reflect both mechanical properties and the thermal conductivity of materials, it still can't characterize the TSR correctly in many situations [18,28,29]. So the heat transfer condition and critical rupture temperature difference are used to characterize the TSR of ZnS plate in the calculation [24,25].…”
Section: Resultsmentioning
confidence: 98%
“…Zirconium-based ceramics belong to a different class of material called as ultrahigh-temperature ceramics (UHTCs), which have a melting point temperature more than 3000 °C. In contradiction to their high melting temperature and impact strength, Feng et al, had reported that monolithic ultrahigh temperature ceramics are brittle materials with low values of fracture toughness and most of all have got poor thermal shock resistance (TSR) . TSR is an important parameter to be tested for the performance of high-temperature ceramics. Many research groups have established that the TSR of a ceramics is sensitive to temperature and other external parameters, while Li et al, had reported that the TSR of UHTC also depends on mechanical and thermal properties and they fail at surfaces when the surface stress due to thermal shock exceed fracture strength. Also mathematical evaluation of mechanical properties have been undertaken for fracture at high time rate of thermal loads based on certain assumptions which state that the model (Figure ) is a two well-bonded plate, which does not consider the interface damage, there is no heat exchange between the UHTC plate and base plate, both the layers geometrically confirm with each other which make calculation easier, finally plate is continuous, isotropic, elastic, and is restricted in the domain of small deformation hypothesis.…”
Section: The Physical Properties Of Ablative Materialsmentioning
confidence: 99%
“…The equations for the effective linear expansion in the ceramic layer then are given by eq : where Δ x 1 is the elongation in the ceramic plate without external restrictions and Δ x σ is the value of restricted elongation due to complementary compressive stress at the interface. From the above equation, it is evident that the net elongation of the system when assumed the changes in Young’s modulus ( Y c ) and Poisson’s ratio (μ c ) for ceramic material are devoid of temperature changes, could generate an internal stress σ in the ceramic plate plausibly at the interface, which was derived by Li et al, as shown in eq : Considering the above equation with the effects of temperature would be modified to eq .…”
Section: The Physical Properties Of Ablative Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the improvement of the thermal shock resistance always means the sacrifice of other material properties of the materials. The thermal shock resistance of the ceramics is not only related to their thermal properties, but also closely related to the interface structure of the ceramic materials [29][30][31][32][33][34]. Based on the microstructure of the wing membrane of dragonfly, Song et al [35] proposed a new method to pattern the surface of ceramics to a biomimetic nano-finned surface.…”
Section: Introductionmentioning
confidence: 99%